Levels of t-PA and PAI-2 in gingival crevicular fluid during orthodontic tooth movement in adults - Hoshino-Itoh Junko; Kurokawa Akihiko; Yamaguchi Masaru; Kasai Kazutaka (Sciendo, 2005)
Background: The regulation of plasminogen activation is a key element in controlling proteolytic events in the extracellular matrix.